2010
DOI: 10.3109/10408444.2010.506638
|View full text |Cite
|
Sign up to set email alerts
|

Review of carbon nanotubes toxicity and exposure—Appraisal of human health risk assessment based on open literature

Abstract: Carbon nanotubes (CNTs) possess many unique electronic and mechanical properties and are thus interesting for numerous novel industrial and biomedical applications. As the level of production and use of these materials increases, so too does the potential risk to human health. This study aims to investigate the feasibility and challenges associated with conducting a human health risk assessment for carbon nanotubes based on the open literature, utilising an approach similar to that of a classical regulatory ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
111
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(115 citation statements)
references
References 114 publications
1
111
1
2
Order By: Relevance
“…This is in contrast to some studies on the genotoxicity of MWCNT (in vivo bone marrow cells upon intraperitoneal injection: Patlolla et al 2010; in vitro human lung cells: Ursini et al 2012; in vitro hamster lung cells: Asakura et al 2010). Overall, the direct genotoxic potential of nanotubes is still considered inconclusive (Aschberger et al 2010). Although the breathing pattern of the allergic rats differed from the healthy rats, this was only true during challenge with TMA, shortly after challenge, and 24 hr after challenge.…”
Section: Discussioncontrasting
confidence: 46%
“…This is in contrast to some studies on the genotoxicity of MWCNT (in vivo bone marrow cells upon intraperitoneal injection: Patlolla et al 2010; in vitro human lung cells: Ursini et al 2012; in vitro hamster lung cells: Asakura et al 2010). Overall, the direct genotoxic potential of nanotubes is still considered inconclusive (Aschberger et al 2010). Although the breathing pattern of the allergic rats differed from the healthy rats, this was only true during challenge with TMA, shortly after challenge, and 24 hr after challenge.…”
Section: Discussioncontrasting
confidence: 46%
“…42 It is important to consider that the effect of CNTs is dependent on intrinsic factors such as formulation, production and endocytosis capacity. 38 This investigation evaluated the effect of the MWCNTs plus TMZ in malignant glial cells and MWCNTs bioavailability in RG2 glioma cells: functionalized MWCNTs were more efficiently endocytosed by RG2 cells than nonfunctionalized MWCNTs. From the FACS analysis, we learned that in vitro cells treated with functionalized MWCNTs alone or in combination with TMZ increased in size compared with control cells (Figure 5A and B).…”
Section: Discussionmentioning
confidence: 99%
“…The MWCNTs used in this study induced cell death in both astrocytes and cultured RG2 cells at all concentrations used (Figures 2 and 3), as has been previously reported. [37][38][39] After observing the results, we decided to use the 50 µg/mL dose for further experiments; at this concentration, all MWCNTs induced a significant percentage of cell death. Considering that the standard treatment for GBM consists in surgical resection accompanied by radiotherapy and chemotherapy with TMZ, 40,41 the next step was to use MWCNTs in combination with TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…20 A 2010 review located eight occupational exposure studies, primarily published in the previous two years. 21 The precautionary principle would apply here even though uncertainty remains about the link between carbon nanotubes and any human or environmental harm. In quantitative risk analysis, only toxicity data for the specific product are relevant.…”
Section: General Guidelinesmentioning
confidence: 99%
“…Traditional risk assessment is further hampered for carbon nanotubes by a lack of knowledge about the use, exposure, and risk management measures already in place for carbon nanotubes. 21 Challenges arise even in preparing carbon nanotubes for toxicity studies, and in drawing implications for human health from animal studies. 22 Based on a traditional risk assessment, reviewers concluded that the carbon toxicity data publicly available up to June 2010 contains substantial uncertainties in terms of exposure and hazard and therefore these results should not be used for any regulatory decisionmaking.…”
Section: General Guidelinesmentioning
confidence: 99%